I want to prove that $(A\setminus B)\setminus(A \setminus C)=(A \cap C)\setminus B $, so I did this:

$ x \in (A \setminus B)\setminus(A \setminus C) \iff $

$ (x \in A \setminus B) \wedge (x \notin A \setminus C) \iff $

$ (x \in A \wedge x \notin B) \wedge (x \notin A \vee x \in C) \iff $

$ (x \in A \wedge x \notin B \wedge x \notin A) \vee (x \in A \wedge x \notin B \wedge x \in C) \iff $

(Now, the statement in the first bracket is always false, so the truth value of the whole disjunction in the line above depends only on the second bracket)

$x \in A \wedge x \notin B \wedge x \in C \iff $
$ x \in (A \cap C) \setminus B $

Is the method correct? Thanks in advance.

  • 1
    $\begingroup$ Looks good to me. $\endgroup$
    – gt6989b
    Oct 7 '19 at 20:29
  • $\begingroup$ I can't find any errors. $\endgroup$ Oct 7 '19 at 20:32

It's correct. A (not so) different way could be to set $U=A\cup B\cup C$ and denoting complementation with respect to $U$ by $X^c$: \begin{align} (A\setminus B)\setminus(A\setminus C) &=(A\cap B^c)\cap(A\cap C^c)^c \\ &=(A\cap B^c)\cap(A^c\cup C)\\ &=(A\cap B^c\cap A^c)\cup(A\cap B^c\cap C)\\ &=\emptyset\cup(A\cap B^c\cap C)\\ &=(A\cap C)\cap B^c\\ &=(A\cap C)\setminus B \end{align} One could also go in a different direction: $$ (A\setminus B)\setminus(A\setminus C)=(A\cap B^c\cap C)=(A\setminus B)\cap C $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.